Biomass consumption and persistent COVID symptoms in patients with moderate and severe SARS-CoV-2 infection - Correa-Coronel , José Raúl (2025)
Biomass consumption causes COPD, but it is unknown if it is linked to Post-Acute COVID-19 Syndrome (PACS). Objective: To examine the association between biomass use and this syndrome in recovered patients from two hospitals in northern Peru. Methods: A descriptive, cross-sectional, exploratory study was carried out. A questionnaire collected sociodemographic data, respiratory symptoms, and biomass use. Results: The final sample consisted of 110 participants. PACS was more common in those aged 35-65 (87.8%) and in Piura (89.1%), occurring in 88.1% of 2021 cases; the median time from symptom onset to interview was 82 (IQR = 79-119) weeks; 97/110 (86.3%) developed PACS; of these, 31% had used biomass before COVID-19 (p = 0.332). Among patients with PACS, the prevalence of dyspnea, fatigue, and cough was 68.4%, 67.3%, and 45.3%, respectively. After COVID-19, 61.05% used salbutamol and 14.7% used home oxygen. In the final model: having had a tracheostomy (p = 0.011), ICU stay (p = 0.039), and the mention of “sequelae in the epicrisis” (p = 0.052) were associated with PACS; however, biomass use (p = 0.332) and years of use (p = 0.072) were not. Conclusion: No link was found between prior biomass use and the development of PACS. The frequency of PACS was high, with dyspnea being the most common symptom.